Professional competence of ASEAN accountants at conference presentations - Fauzanna, Wulan; T'Chiang, Chow Ung; Hashim, Azirah (Indonesian Journal of Applied Linguistics, 2024)
The ASEAN Federation of Accountants (AFA) organizes the Continuing Professional Development (CPD) programs to enhance the professional competence of ASEAN accountants. One of the CPD programs is the conference presentation (CP). The conference is the way the AFA shares its new frameworks and policies. Consequently, this language-based professional practice and competence has become an important need. In the presentation, this language-based professional competence is an important need. However, it received limited attention from an Applied Linguistics perspective. To study the professional practice and professional competence of the accountants in the AFA CP, the research used Genre Analysis to analyze the moves and Metadiscourse analysis to analyze specific markers used in the presentations. The software Wordsmith 8.0 (Scott, 2020) is applied for concordance analysis. Thirteen conference presentations given by accountants from the ASEAN region were collected from an AFA conference conducted in Indonesia. The presentations were recorded and transcribed with the software Wreally.com (Wreally, 2019). The text was analyzed based on Seliman and Dubois's (2002) move structure and Hyland’s (2005, 2019) interpersonal metadiscourse markers. The findings revealed the tendency to use more interactional resources than interactive resources to connect information and assist the audience in understanding the problem-solution-modeled presentations. The popular interactional resources are Self-mention, Engagement markers, and Hedges while the interactive resources are Transition markers. This study found that the discipline, the problem-solution convention, the presenter-audience interaction, and the preferred usage of certain markers determined the use of metadiscourse markers for the AFA CP. It helps accountants understand the importance and need of using moves and metadiscourses in developing their professional competence. The study contributes to the literature in English for Specific Purposes (ESP) and serves as a guide in presenting effectively at conferences and developing purposeful CPD training. This research can also be replicated in studies on professional competence of other professions and professional training programs.